INFLUENCE OF FAMILY TYPE AND PERSONALITY CHARACTERISTICS ON JUVENILE DELINQUENCY AMONG SECONDARY SCHOOL STUDENTS OF KUBWA BWARI AREA COUNCIL FCT ABUJA NIGERIA - Enenta, Francisca Nkechi; Iwuala, Caleb Chukwuebuka; Osuocha, Onyekachi Chilerem (African Journal of Social and Behavioural Sciences, 2024)
This study investigated the influence of family type and personality characteristics on juvenile delinquency among secondary school students in Kubwa, Bwari Area Council, FCT Abuja, Nigeria. Employing the Cross-Sectional Survey design, 200 adolescent secondary school students participated, selected through systematic random sampling. 12-17 years. Participants comprised of 90 males and 110 females with a mean age of 14.96 years (SD=1.12). The Self-Report Delinquency Scale and Big Five Inventory (BFI) were utilized for data collection, with three hypotheses tested using independent t-tests, Simple Linear Regression, and Multiple Regression analyses. Findings revealed no significant difference in delinquency rates between single-parent and nuclear families. However, personality traits significantly influenced juvenile delinquency among the students. Additionally, a significant joint influence of personality characteristics and family type on delinquency was observed. It was concluded that while there is no significant difference in delinquency between single-parent and nuclear families, personality traits, both individually and in conjunction with family type, are significant determinants of juvenile delinquency. The study recommends implementing support programs for parents, educating families on the psychological effects of broken homes, establishing structured assessments of adolescent personality traits, and encouraging further research for validation and deeper understanding.